Analysis of the microbial population dynamics during spontaneous and controlled fermentation of Chili "Charapita" (Capsicum frutescens) - Vegas, Carlos (2016)
Chilies are the main ingredients of the Peruvian gastronomy. Chili "Charapita" (Capsicum frutescens) is very used in amazon food. The last decade, "the gastronomic boom" has increased their demand, so it is necessary to develop new technologies for their preservation sustainably, healthy, without affecting the environment. The aim of the present work was to analyze the microbial population dynamics during Chili "Charapita" fermentation using spontaneous (SF) and controlled (CF) fermentation. Fermentations were conducted at pilot scale and room temperature with chilies from Iquitos city. A lactic acid bacteria (LAB) strain type belonging to Lactobacillus plantarum ATCC 14917 was used in FC. Fermentations were monitored through reducing sugars, acidity and pH determinations. Microbial tests were performed: total cells count by microscopy and microbial growth in culture media. LAB, yeasts, enterobacteriaceae and pseudomonas were recovered in MRS, YPD, McConkey and Cetrimide media, respectively. Both fermentations finalized at 47 days, reducing sugars were below 0.5 g/L and 3.07 3.11 of pH. However, the acidity in SF was higher than CF (1.58% vs. 1.20%). At microbiological level, LAB and yeasts were microorganisms responsible for SF. However, starter LAB was not suitable for CF. In fact, it was replaced by yeasts and enterobacterias. So, the use of autochthonous microorganisms of the fermentation as starter is important for a better fermentation control.